(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Characteristic of money laundering phenomenon is a compound and complex nature like the style of regular crimes . These operations are planned and excuted with those who have high quality experiences to hide the evidences of their deeds so They ask the help of financials ,economicals and legists to plan for money laundering. Banks are important and suitable places for illegal circulation of money because of the different types of accounts , rapidity and overlap which emphasis of its main duty to dislocate illegal money which comes from illegal sources without adding legal characteristic to it . Here we should explain the important role of banks in striving the phenomenon –Bank should try to show and analyze inward procedures and ensure if these procedures are enough in stirving money laundering or not . In addition, they should show some practical deeds that indicate suspected operations which may simplify money laundering by banks.